One-pot multicomponent synthesis of bis(diamino-1,3,5-triazines) under microwave irradiation. - Muhammad Syafiq, Sahari; Tiekink, Edward R. T. *; Dolzhenko, Anton V (Wiley, 2022)
A new method for the synthesis of bis(1,3,5-triazine-2,4-diamines) was developed using a one-pot multicomponent approach. The synthesis was performed using the acid-catalyzed reaction of cyanoguanidine with amines and aldehydes, followed by dehydrogenative aromatization of the dihydrotriazine intermediates upon heating with alkali. Two types of bis(1,3,5-triazine-2,4-diamines) were prepared using either piperazine as the bifunctional amine or terephthaldehyde as the bifunctional aldehyde thus affording products with a piperazine or p-phenylene link between two 1,3,5-triazine rings. The microwave-assisted method allows fast and convenient synthesis of diverse bis(1,3,5-triazine-2,4-diamines).